Diagnostic utility of C reactive protein and widal test with hematological parameters for sepsis in children attending a tertiary care hospital, South India - Dr. Dhananjaya C.D.; Dr. Sunil B.N. (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Sepsis is a major problem in Children and Clinical criteria alone could not establish the diagnosis of childhood sepsis. It is extremely important to make an early diagnosis of sepsis for the prompt institution of antimicrobial therapy, which improves outcomes.Objective: The aim of this study is to determine the diagnostic utility of C - reactive protein (CRP) in combination with hematological parameters of CBC as early diagnostic marker in detection infections in children.Methodology: This prospective study was conducted on children attending pediatric OPD or admitted as inpatient at Oxford Medical College Hospital, Bengaluru, Karnataka. Blood specimens were obtained from each child prior to commencement of antibiotics for sepsis work up and subjected to CBC, CRP and Widal test.Results: 274 (54.4%) out of 503 children were boys and majority 77.9% of the study population were belonging to Under 5 age group. The mean difference observed between the groups of CRP positive and negative children for all the components of the Complete Blood Count was statistically significant except for Monocytes and Eosinophils which tells that these variables were significant predictors of sepsis in the children.Conclusion: The combination of total WBC count along with CRP could be a reliable diagnostic tool to detect the presence of Infections in children. Routine ordering of CRP for detection of Infection in febrile children will increase the probability of correct diagnosis and help the pediatrician in more accurate and effective management of sepsis in children.